Respuesta :
To do this, you use the FOIL method.
F: front
x*x=x^2
O: outer
x*-4=-4x
I: inner
6*x=6x
L: last
6*-4=-24
Add all those up and you get:
x^2-4x+6x-24
Which is equal to:
x^2+2x-24
Hope this helped!
F: front
x*x=x^2
O: outer
x*-4=-4x
I: inner
6*x=6x
L: last
6*-4=-24
Add all those up and you get:
x^2-4x+6x-24
Which is equal to:
x^2+2x-24
Hope this helped!
use foil or just plain distribute
if you want foil
FOIL
First
Outer
Inner
Last
that is order to multiply dem numbers
(x+6)(x-4)
First: x times x=x²
Outer: x times -4=-4x
Inner: 6 times x=6x
Last: 6 times -4=-24
add them all together
x²-4x+6x-24
x²+2x-24
if you want foil
FOIL
First
Outer
Inner
Last
that is order to multiply dem numbers
(x+6)(x-4)
First: x times x=x²
Outer: x times -4=-4x
Inner: 6 times x=6x
Last: 6 times -4=-24
add them all together
x²-4x+6x-24
x²+2x-24